Management of Pediatric Condyle Fractures. Issue 7 (October 2019) - McGoldrick, David M.; Parmar, Paras; Williams, Rhodri; Monaghan, Andrew; McMillan, Kevin
Abstract : Introduction: Mandibular condyle fractures are a common type of facial fracture in children. The authors aimed to examine the demographics, etiology, treatment, and outcomes of these fractures managed in a single pediatric trauma unit. Materials and Methods: A retrospective review was performed of patients presenting to a pediatric hospital between 2003 and 2016 with mandibular condyle fractures. Initial data was extracted from a dedicated trauma database. Included patient's medical records and imaging were then reviewed. Data on demographics, etiology, fracture type, and treatment were recorded. Univariate statistical analysis was performed. Results: Forty-four patients with 49 condyle fractures were included. The average age of patients was 11.4 years (range 3–15 years). A fall from a bicycle/scooter was the most common mechanism. Twenty-six fractures were isolated and 23 involved a further fracture of the mandibular arch. The condylar neck was the most common site of fracture (55%). There was no statistical significance between age (0–10 years, 10–16 years) and site of fracture or the presence of an associated arch fracture. The majority of isolated fractures (73%) were treated conservatively without inter-maxillary fixation. Thirty-nine patients attended the follow-up and the median follow-up period was 196 days (interquartile range 21–165 days). Two patients had a malocclusion at follow-up that required intervention. Conclusion: There was a broad range of presentations in our cohort. Conservative management in isolated fractures resulted in stable outcomes and this large case series supports the consensus that management of pediatric condyle fractures should be as conservative as possible. Abstract : Supplemental Digital Content is available in the text